Identification of Components of the Hippo Pathway in Hydra and Potential Role of YAP in Cell Division and Differentiation - Unni, Manu; Reddy, Puli Chandramouli; Pal, Mrinmoy; Sagi, Irit; Galande, Sanjeev (Frontiers in Genetics, 2021)
The Hippo signaling pathway has been shown to be involved in the regulation of cellular identity, cell/tissue size maintenance and mechanotransduction. The Hippo pathway consists of a kinase cascade which determines the nucleo-cytoplasmic localization of YAP in the cell. YAP is the effector protein in the Hippo pathway which acts as a transcriptional cofactor for TEAD. Phosphorylation of YAP upon activation of the Hippo pathway prevents it from entering the nucleus and hence abrogates its function in transcription of the target genes. In Cnidaria, the information on the regulatory roles of the Hippo pathway is virtually lacking. Here, we report for the first time the existence of a complete set of Hippo pathway core components in Hydra. By studying their phylogeny and domain organization, we report evolutionary conservation of the components of the Hippo pathway. Protein modelling suggested conservation of YAP-TEAD interaction in Hydra. Further, we characterized the expression pattern of the homologs of yap, hippo, mob and sav in Hydra using whole mount RNA in situ hybridization and report their possible role in stem cell maintenance. Immunofluorescence assay revealed that Hvul_YAP expressing cells occur in clusters in the body column and are excluded in the terminally differentiated regions. Actively proliferating cells marked by Ki67 exhibit YAP co-localization in their nuclei. Strikingly, a subset of these co-localized cells are actively recruited to the newly developing bud. Disruption of the YAP-TEAD interaction increased the budding rate indicating a critical role of YAP in regulation of cell proliferation in Hydra. Collectively, we posit that the Hippo pathway is an important signaling system in Hydra, its components are ubiquitously expressed in the Hydra body column, and play crucial role in Hydra tissue homeostasis.